Adsorption Studies of Acetic Acid on the Surface of Solanum nigrum - HUSSAIN, SAYYED; MERAJ, AYESHA; RUHI TABASSUM, SIDDIQUI (Asian Journal of Chemistry, 2010)
The object of the present investigation is to study the adsorption of acetic acid on Solarium nigrum. The effect of certain parameters on adsorption has been studied. Applicability of Fruendlich adsorption isotherm and Langmuir adsorption isotherm has been tested. Various thermodynamic parameters such as ΔG, ΔH and ΔS are reported. The adsorption power of Solanum nigrum is calculated. The experiments are carried out using batch adsorption process.